2023
DOI: 10.1038/s41598-023-45950-2
|View full text |Cite
|
Sign up to set email alerts
|

Using a Bayesian hierarchical approach to study the association between non-pharmaceutical interventions and the spread of Covid-19 in Germany

Yeganeh Khazaei,
Helmut Küchenhoff,
Sabine Hoffmann
et al.

Abstract: Non-Pharmaceutical Interventions (NPIs) are community mitigation strategies, aimed at reducing the spread of illnesses like the coronavirus pandemic, without relying on pharmaceutical drug treatments. This study aims to evaluate the effectiveness of different NPIs across sixteen states of Germany, for a time period of 21 months of the pandemic. We used a Bayesian hierarchical approach that combines different sub-models and merges information from complementary sources, to estimate the true and unknown number o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Enhanced surveillance is commonplace in all regions where it has shown efficacy. Furthermore, a German study indicated that combined general behavioural changes were the most effective non-pharmaceutical intervention [26].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced surveillance is commonplace in all regions where it has shown efficacy. Furthermore, a German study indicated that combined general behavioural changes were the most effective non-pharmaceutical intervention [26].…”
Section: Introductionmentioning
confidence: 99%